2020
DOI: 10.1111/csp2.281
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low‐cost consumer‐grade UAVs for conducting comprehensive high‐frequency population censuses of hippopotamus populations

Abstract: The hippopotamus Hippopotamus amphibious (hereafter referred to as hippo) is classified as vulnerable according to the IUCN Red data list. They play a significant role in aquatic systems as allochthonous nutrient providers, and as facilitators and competitors in grasslands. Traditional census methodologies for hippo are difficult and costly to repeat. Previous research has been conducted on the use of unmanned aerial systems (UASs) to conduct hippo population estimates; however, findings either needed justific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Observations during the wet season show H. amphibius mostly submerge in pools, therefore reducing visibility and researchers' ability to detect and count them. Several studies have confirmed this observation challenge during H. amphibius census in wet seasons, suggesting higher counts during the dry season than the wet season when water levels are higher (Olivier and Laurie 1974;Martin 2005;Kujirakwinja 2010;Zisadza et al 2010;Lhoest et al 2015;Fritsch and Downs 2020). Counts in the dry season are suggested to produce a reliably valid estimate of the H. amphibius population (Timbuka 2012).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Observations during the wet season show H. amphibius mostly submerge in pools, therefore reducing visibility and researchers' ability to detect and count them. Several studies have confirmed this observation challenge during H. amphibius census in wet seasons, suggesting higher counts during the dry season than the wet season when water levels are higher (Olivier and Laurie 1974;Martin 2005;Kujirakwinja 2010;Zisadza et al 2010;Lhoest et al 2015;Fritsch and Downs 2020). Counts in the dry season are suggested to produce a reliably valid estimate of the H. amphibius population (Timbuka 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Ground counts survey techniques (land-and boat-based counts) provide comparatively accurate results to record changes in H. amphibius numbers and distribution. Hippopotamus amphibius census during this study were carried out at different periods of the year to determine the seasonal differences in population sizes (Olivier and Laurie 1974;Martin 2005;Kujirakwinja 2010;Zisadza et al 2010;Timbuka 2012;Lhoest et al 2015;Fritsch and Downs 2020). We followed the ground counts method as described by Kujirakwinja 2010 andMartin 2005 to estimate the number of H. amphibius in the Bui National Park from August 2020 to July 2021.…”
Section: Hippopotamus Amphibius Surveymentioning
confidence: 99%
“…Yet, where they still occur, they have large impacts and continue to shape present-day ecosystems. Moreover, 'ghosts' of ecosystem engineers past continue to affect contemporary landscapes and by studying extant engineering species we stand to gain valuable insights into these legacy effects and how they continue to affect current-day ecosystem functioning (Frauendorf et al, 2021;Albertson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Population-level studies of large herbivores are commonly carried out using aerial surveys with manned aircraft (e.g. Caughley, 1974;Vucetich & Peterson, 2004), which is often nancially prohibitive and can prevent the necessary amount of spatial or temporal replications for accurate and frequent estimates needed for decisions in conservation (Ferreira & Aarde, 2009;Fritsch & Downs, 2020). Recently, drones (Unmanned Aerial Systems or Remotely Piloted Aircraft) have emerged as an accessible, safe, and cost-effective alternative for aerial surveys and have been tested to sample large herbivore populations (e.g.…”
Section: Introductionmentioning
confidence: 99%